2021
DOI: 10.4269/ajtmh.21-0551
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 in Uganda across Two Epidemic Phases: A Prospective Cohort Study

Abstract: Among a prospective cohort of children and adults admitted to a national COVID-19 treatment unit in Uganda from March to December 2020, we characterized the epidemiology of and risk factors for severe illness. Across two epidemic phases differentiated by varying levels of community transmission, the proportion of patients admitted with WHO-defined severe COVID-19 ranged from 5% (7/146; 95% CI: 2–10) to 33% (41/124; 95% CI: 25–42); 21% (26/124; 95% CI: 14–29%) of patients admitted during the peak phase received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
3
10
2
Order By: Relevance
“…Similar low frequency for SARS-CoV-2 and malaria co-infections found in our study (1%) has been also reported in other studies (3438) ( Supplementary Table 4 ). A systematic review of COVID-19 and malaria coinfection studies has estimated 11% of pooled prevalence (data of 5 studies) with a high degree of heterogeneity (39).…”
Section: Resultssupporting
confidence: 92%
“…Similar low frequency for SARS-CoV-2 and malaria co-infections found in our study (1%) has been also reported in other studies (3438) ( Supplementary Table 4 ). A systematic review of COVID-19 and malaria coinfection studies has estimated 11% of pooled prevalence (data of 5 studies) with a high degree of heterogeneity (39).…”
Section: Resultssupporting
confidence: 92%
“…Similar low frequency for SARS-CoV-2 and malaria co-infections found in our study (1.9 %) has been also reported in other studies ( 37 41 ) ( Supplementary Table S4 ). A systematic review of COVID-19 and malaria coinfection studies has estimated 11% of pooled prevalence (data of 5 studies) with a high degree of heterogeneity ( 42 ).…”
Section: Resultssupporting
confidence: 91%
“… 39 , 40 More than half of our study participants were < 50 years of age. Our age distribution was similar to other treatment centers in Ethiopia 32 , 34 , 35 and data from other sub-Saharan countries, 41 43 but younger than study populations reported from Europe, North America, and China. 44 This variation could be due to the generally younger population of the African continent and greater hospital admissions in the region early during the pandemic for those with mild COVID-19 disease.…”
Section: Discussionsupporting
confidence: 87%